Reserving Cultural Heritage Through Traditional Filipino Games - Shopia Charlize; Gilbert Ryan Semilla; Md. Enayet Hossain (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to explore efforts by government and non-governmental organizations to preserve Traditional Filipino Games and examine whether Filipino children still play, understand, and prefer these games over digital alternatives. Methodology: This study used document analysis and literature review methods, examining prior research including surveys by Booc et al. (2019) and experimental data from Santos et al. (2019). Quantitative data was processed using SPSS and paired samples t-tests to assess mobile games' impact on student understanding. Main Findings: Efforts to preserve traditional games include Magna Kultura's Larong Pinoy Program and legislative support via House Bill 8626. Some children still play and value these games for cultural and social reasons. Mobile gaming apps showed mixed effectiveness; only the game Luksong Baka showed significant improvement in understanding, indicating potential but limited digital preservation success. Novelty/Originality of this study: This study uniquely synthesizes grassroots, academic, and governmental perspectives on preserving cultural heritage through traditional games. It highlights the digitalization of indigenous play as both a preservation tool and educational strategy, offering a multidisciplinary approach to cultural sustainability in the face of modern technological influence.